Habenula Circuit Development: Past, Present, and Future - Beretta, Carlo A.; Dross, Nicolas; Gutierrez-Triana, Jose A.; Ryu, Soojin; Carl, Matthias (Frontiers in Neuroscience, 2012)
The habenular neural circuit is attracting increasing attention from researchers in fields as diverse as neuroscience, medicine, behavior, development and evolution. Recent studies have revealed that this part of the limbic system in the dorsal diencephalon is involved in reward, addiction and other behaviors and its impairment is associated with various neurological conditions and diseases. Since the initial description of the Dorsal Diencephalic Conduction system (DDC) with the habenulae in its center at the end of the 19th century, increasingly sophisticated techniques have resolved much of its anatomy and have shown that these pathways relay information from different parts of the forebrain to the tegmentum, midbrain and hindbrain. The first part of this review gives a brief historical overview on how the improving experimental approaches have allowed the stepwise uncovering of much of the architecture of the habenula circuit as we know it today. Our brain distributes tasks differentially between left and right and it has become a paradigm that this functional lateralization is a universal feature of vertebrates. Moreover, task dependent differential brain activities have been linked to anatomical differences across the left-right axis in humans. A good way to further explore this fundamental issue will be to study the functional consequences of subtle changes in neural network formation, which requires that we fully understand DDC system development. As the habenular circuit is evolutionarily highly conserved, researchers have the option to perform such difficult experiments in more experimentally amenable vertebrate systems. Indeed, research in the last decade has shown that the zebrafish is well suited for the study of DDC system development and the phenomenon of functional lateralization. We will critically discuss the advantages of the zebrafish model, available techniques and others that are needed to fully understand habenular circuit development.